Analisis Kebutuhan Pengembangan E-Modul Berbasis Kearifan Lokal Tanaman Obat Pada Sistem Pencernaan - Laila Witra; Sepita Ferazona; Nurkhairo Hidayati (CV. SINAR HOWUHOWU, 2026)
ABSTRAK This study aims to analyze students’ and teachers’ needs for the development of a biology e-module based on local wisdom of medicinal plants in the digestive system topic. The research employed a mixed-methods approach with a sequential exploratory design, beginning with qualitative data collection followed by quantitative data collection. Qualitative data were obtained through interviews and observations involving an eleventh-grade biology teacher at SMAN 11 Pekanbaru, while quantitative data were collected using a needs analysis questionnaire administered to 33 eleventh-grade students. The questionnaire was developed based on four indicators: the need for engaging and interactive learning materials, the integration of local wisdom related to medicinal plants, the design and features of the e-module, and contextual and applicative learning approaches. Quantitative data were analyzed using percentage techniques. The results showed that students required engaging and interactive digital learning materials (69.21%), the integration of local wisdom related to medicinal plants in biology learning (78.30%), and strongly required e-modules with attractive designs and features (84.36%) as well as contextual learning approaches (82.79%). Furthermore, teacher interview results indicated that although the Merdeka Curriculum has been implemented and local wisdom values have been integrated through the Pancasila Student Profile, the utilization of medicinal plants as learning resources in the digestive system topic has not been optimally implemented. Therefore, the development of a biology e-module based on local wisdom of medicinal plants is considered essential as an instructional innovation to support contextual learning, enhance students’ conceptual understanding, and foster scientific attitudes.